Efeito do tratamento com IL-3, IL-7 OU IL-9 em camundongos experimentalmente infectados com Trypanosoma cruzi - Alves, Rosiane Nascimento (2015)
Chagas disease, caused by the protozoan Trypanosoma cruzi, is ranked as the most serious parasitic disease in Latin America and has become a worldwide problem. A bulk of studies substantiates that Th1-associated cytokines are essential elements in early resistance against the parasite and are associated with the development of the chronic cardiac form. Although cytokines have a key role in the immune response against T. cruzi, little is known about IL-3, IL-7 and IL-9 in this context. Then the aim of this study was to analyze the role of IL-3, IL-7 and IL-9 in the acute phase of T. cruzi experimental infection. For this purpose, parameters indicative of improvement in clinical status of the animals both infected and treated as just treated were studied, such as: morbidity, mortality and histopathology. The amount of cardiac mast cells and the serum cytokines profile were also evaluated. Our data revealed that the treatment with IL-3, IL-7 or IL-9 did not alter the clinical parameters analyzed or the amount of cardiac mast cells in mice infected with T. cruzi. However the treatment with IL-3 decreased the cardiac T. cruzi-induced inflammation and the treatment with IL-7 increased serum levels of IL-5 in infected animals. In addition, the treatment with IL-9 increased the serum levels of Th1 cytokine profile (IL-2, IFN-y and TNF-α) and decreased cardiac fibrosis in infected animals, suggesting a possible protective role of this cytokine in this context. Taken together, our results underline the importance of these cytokines in modulation of T. cruzi infection. Since studies involving IL-3, IL-7 and IL-9 activity during Chagas disease are critical in understanding the parasite control process and the protective and/or harmful action of these cytokines in the host. In addition, understanding of the immunological mechanisms mediated by these cytokines that are involved in disease development may contribute to the establishment of new therapeutic interventions to prevent Chagas disease and treat their symptomatic forms.